FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN MAHASISWA AKUNTANSI DALAM BERWIRAUSAHA: FACTORS AFFECTING ACCOUNTING STUDENT DECISION MAKING IN ENTREPRENEURSHIP - Aulia, Garinda; Hardiningsih, Pancawati (Universitas Riau, 2023)
The goal of this study is to investigate and look at how e-commerce, business capital, accounting information systems, income expectations, and entrepreneurial decision-making relate. Students enrolled in the Semarang Stikubank University (UNSBANK) Accounting Study Program for the classes of 2019 and 2020 made up the study's population. The primary data used in this study was directly collected from respondents using a Google form. A questionnaire is a method of gathering data. 130 respondents were included in the sample that was collected using the purposive sampling technique. The analytical technique employed is multiple linear regression analysis. According to the test's findings, e-commerce, accounting information systems, and income expectations have a effect and significant impact on entrepreneurs' ability to make decisions, however business capital has no such impact.